2000
DOI: 10.2355/isijinternational.40.172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on Fracture Mechanisms in Galvannealed Coatings.

Abstract: Fracture mechanisms in galvannealed coatings have been studied by performing draw bead tests on galvannealed Ti stabilized interstitial free and Aluminum killed low carbon steel sheets and by investigating coating microstructures by scanning electron microscopy. Galvannealing treatments, on samples galvanized using an industrial hot-dip galvanizing process, were conducted at 450, 500 and 550°C for several time periods between 1 and 360 s in a laboratory induction furnace.In the coatings with low Fe content (up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…The coating layer exhibits multiple cracking under thermally induced stress during cooling from the heat treatment-to room-temperature due to the difference in thermal expansion between the coating layer and substrate steel. 1,[4][5][6][7][8][9][10] When tensile stress is applied, the multiple cracking progresses furthermore, 1,[4][5][6][7][8][9][10][11] as typically shown in Fig. 1, and then, as shown later, the coating layer is spalled.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coating layer exhibits multiple cracking under thermally induced stress during cooling from the heat treatment-to room-temperature due to the difference in thermal expansion between the coating layer and substrate steel. 1,[4][5][6][7][8][9][10] When tensile stress is applied, the multiple cracking progresses furthermore, 1,[4][5][6][7][8][9][10][11] as typically shown in Fig. 1, and then, as shown later, the coating layer is spalled.…”
Section: Introductionmentioning
confidence: 99%
“…1, and then, as shown later, the coating layer is spalled. 1,6,7,[12][13][14][15][16][17][18][19][20][21] Concerning the thermal and applied stress-induced multiple cracking of the coating layer, the authors [8][9][10][11] have recently measured the change of crack spacing with increasing applied strain e for two samples supplied as the common samples for the research group on structure and property of the coating on GA (galvannealed) steels, organized in The Iron and Steel Institute of Japan. One was the IF (Interstitial Free) steel substrate with 10 mm thickness-coating layer (hereafter noted as IF/10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hertveldt et al 9) demonstrated in single lap shear test that as the shear strength of galvannealed coatings increased, the amount of fracture at the GFe interface decreased, and also the fraction of the fracture in the a-Fe grain boundaries and within the coating increased. Alpas et al 10) observed in draw bead test that the decohesion occurred along the G-Fe interfaces or along the a-Fe grain boundaries of substrates when Fe contents in coatings are low, i.e., Ͻ5 g/m 2 , while the decohesion occurred along the G-G 1 and the G-d 1 phase boundaries when Fe contents in coatings are between 6 and 9 g/m 2 . The deformation and fracture of the coating is assumed to be thus dependent on the microstructure of the coating and also deformation condition (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the cracks induced parallel to the tensile direction (namely the cracks in the sample width direction) were caused by the thermally induced residual stress. [13][14][15][16][19][20][21] However, the influences of the crack spacing in the tensile direction and that in the sample width direction have not been clarified until now, despite the importance to clarify the spalling behavior. In our recent study, concerning the fracture of GA coating layer with high tensile strength steel substrates, it was newly suggested that the interfacial debonding could be reduced through the enhancement of multiple cracking.…”
Section: Introductionmentioning
confidence: 99%